Perfil em ácidos graxos do tecido hepático de ratos submetidos a dieta cetogênica rica em trienatina - Melo, Ingrid Sofia Vieira de (2011)
Dietary lipids determine the incorporation and fatty acid composition of the organism, especially in organs most susceptible to its modulating action on membrane phospholipids esterified fatty acids, such as the liver. Ketogenic diets, widely used to treat various disorders, often use long-chain triacylglycerols, however, medium chain triglycerides are considered an alternative source, since they are digested, absorbed, oxidized and removed from circulation more rapidly than long chain triacylglycerols. In addition, it lead to the formation of ketone bodies quickly, without the influence of hormonal or nutritional factors. To contribute to the discussion, this paper presents a review chapter, entitled Mitochondrial dysfunction in nonalcoholic fatty liver disease, which gathers information on oxidative stress and consequent mitochondrial dysfunction in the context of liver disease. It also presents an original article, entitled Fatty acid profile in liver tissue of rats subjected to ketogenic diet rich in trienantin, which discusses the effects of a ketogenic diet based on trienantin, a homogeneous triacylglycerol composed of enantic (heptanoic) acid, or based on soybean oil on this profile. The livers of animals fed the ketogenic diet showed a significant reduction in the concentration of monounsaturated fatty acids, 9-hexadecenoic and 9-octadecenoic compared to control group, suggesting a potential reduction in the activity of the enzyme Stearoil-CoA Desaturase 1. Additionally, the group fed trienantin showed increased levels of octadecanoic acid compared to control group, which corroborated the hypothesis of decreased enzyme activity in this group. Thus trienantin in ketogenic proportions exerted modulatory effects similar to soybean oil, widely used conventional oil, despite the differences in fatty acid composition between these two fat sources. The study showed that rats fed a ketogenic diet experienced modulation of fatty acid profile of hepatic lipids and that in the conditions set forth herein, this modulation was due especially to the nature of the ketogenic diet itself and not to the type of oil used in their preparation.